Usefulness of National Service Scheme in physiotherapy curriculum: A mixed-methods study - Dharmayat, Snehal (Journal of Society of Indian Physiotherapists, 2022)
Background and Objectives: National Service Scheme (NSS), as an elective subject in higher education, was introduced in the year 2016 by the University Grants Commission (UGC). From being a practical/activity done by students, it was changed to a theory subject. Ascertaining its acceptance and usefulness becomes essential in the process of program evaluation and for implementing curricular reforms. Materials and Methods: Evidence related to students’ awareness of NSS, its importance in the curriculum, and their perception of the subject were obtained from 279 undergraduate and postgraduate physiotherapy students combined and analyzed. Results: 99.6% of students were aware of NSS. 98.99% responded that it was important in the curriculum, whereas 79.2% of participants reported that they would choose it as an elective subject. The common explanations cited by the students included “helping them understand community better” (98.56%) and “helping them become better individuals” (personality development) (98.92%). Conclusion: NSS finds more acceptance as an activity performed by students (community awareness programs) rather than as a theory subject. It has better acceptance among students inclined toward community/social service.